A pipeline for monitoring water pollution: The example of heavy metals in Lombardy waters - Marco Zanchi; Stefano Zapperi; Chiara Zanotti; Marco Rotiroti; Tullia Bonomi; Stefano Gomarasca; Stefano Bocchi; Caterina A.M. La Porta (Heliyon, 2022)
Time-dependent geolocalized analysis of pollution data allows to better understand their dynamics over time and could suggest strategies to restore a good ecological status of contaminated area. This research analyzes concentrations of pollutants in surface waters and groundwater monitored by the Regional Environment Protection Agency of Lombardy from 2017 to 2020. Lombardy is one of the richest and populous region of Europe, providing an interesting example of the impact of environmental pollutants due to anthropogenic and industrial activities, not only for Italy but also for all Europe. Results show that groundwater displays more sites with heavy metals above the legal limit with respect to surface waters, including As, Ni, Cr and Zn. Furthermore, the spatio-temporal analysis of the data clearly shows that the introduction of more restrictive laws is a proper policy to improve the ecological status of the water.